2017
DOI: 10.1088/2053-1583/aa5521
|View full text |Cite
|
Sign up to set email alerts
|

Brightening of dark excitons in monolayers of semiconducting transition metal dichalcogenides

Abstract: We present low temperature magneto-photoluminescence experiments which demonstrate the brightening of dark excitons by an in-plane magnetic field B applied to monolayers of different semiconducting transition metal dichalcogenides. For both WSe2 and WS2 monolayers, the dark exciton emission is observed at ∼50 meV below the bright exciton peak and displays a characteristic doublet structure which intensity is growing with B 2 , while no magnetic field induced emission peaks appear for MoSe2 monolayer. Our exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
250
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(294 citation statements)
references
References 51 publications
34
250
3
Order By: Relevance
“…Stronger doping may affect the band structure and such effects are not accounted for in our calculations. Interestingly, the experimental results of Molas et al [21] for WSe 2 reveal some differences with earlier measurements. In particular, the bright trion is found to have a binding energy of more than 50 meV.…”
Section: Dark Excitations In Monolayer Transition Metal Dichalcogenidescontrasting
confidence: 62%
See 3 more Smart Citations
“…Stronger doping may affect the band structure and such effects are not accounted for in our calculations. Interestingly, the experimental results of Molas et al [21] for WSe 2 reveal some differences with earlier measurements. In particular, the bright trion is found to have a binding energy of more than 50 meV.…”
Section: Dark Excitations In Monolayer Transition Metal Dichalcogenidescontrasting
confidence: 62%
“…However, basic optical properties such as photoluminescence intensities, exciton decay rates, valley scattering, etc., will depend strongly on the interplay between the bright and dark states in the low-energy part of the spectra [17][18][19]. In recent experiments by Zhang et al [20] and Molas et al [21], it has been shown that dark excitations can be experimentally probed by applying an in-plane magnetic field. Due to the resulting mixture of dark and bright states, they become visible in photoluminescence.…”
Section: Dark Excitations In Monolayer Transition Metal Dichalcogenidesmentioning
confidence: 98%
See 2 more Smart Citations
“…Here, charge tunable samples [66] or experiments in transverse magnetic fields [67,68] are expected to give a better indication on the dark-bright order in future experiments on these narrow linewidth samples. The temperature dependence of the PL peak position follows a standard hyperbolic cotangent relation [69]:…”
Section: B Temperature-induced Line Broadeningmentioning
confidence: 99%